Abnormal balance control mechanisms during dynamic reaching forward and quiet standing in patients with anterior cruciate ligament reconstruction - Wang, Wei; Li, Xudong; Shi, Runxiu; Wang, Cheng; Zhang, Ke; Ren, Xiaomin; Wei, Hui (Frontiers in Physiology, 2023)
Purpose: Postural instability and decreased balance control ability have been observed in patients after anterior cruciate ligament (ACL) reconstruction. Herein, we examined the abnormal balance control mechanisms of these patients during dynamic reaching forward and quiet standing, providing a quantitative index for rehabilitation assessment. Methods: We enrolled ACL reconstruction patients 6-8 months after surgery, and 14 gender-and agematched healthy volunteers. The IKDC and Lysholm were applied in each patient after ACL reconstruction. All participants conducted the quiet standing and reaching forward (RF) tests at the specified locations on force plates. The ground reaction force, center of pressure (COP), and kinematics signals were recorded. The maximal reach distance (MRD), speed of RF, length of COP, peak speed of COP in anterior-posterior direction (AP-COP), and weight bearing ratio (WBR) of the affected limb were calculated in the RF test. The COP speed, COP amplitude, frequency components of COP and WBR were extracted during quiet standing.Results: We observed that the speed of RF in the patients after ACL reconstruction was significantly lower than that of controls (p<0.05). The COP length during RF was positively correlated with the Lysholm scale in the affected limb of patients (r=0.604, p<0.05). The peak of AP-COP speed during RF in the affected limb of patients was significantly lower than that of the healthy controls (p<0.05), and positively correlated with the IKDC scale (r=0.651, p<0.05). WBR on the affected limb of patients during RF were significantly lower than that of controls (p<0.05). The mean (r=-0.633, p<0.05) and peak (r=-0.643, p<0.05) speeds of COP during quiet standing were negatively correlated This is a provisional file, not the final typeset article with the IKDC scale value. The amplitude of AP-COP on the contralateral side of patients was significantly higher than that of controls during quiet standing (p<0.05).Patients after ACL reconstruction performed decreased postural control capacity, especially in dynamic balance, and were accompanied by deficiencies in proprioception. The COP length, peak speed of COP during RF and COP speed during quiet standing could be considered as quantitative index of balance function assessment after ACL reconstruction.